Reformulation of Livelihood in Islamic Family Law: Qur’anic Basis and Women’s Dual Roles - Ridwan, Ridwan; Ismail, Hidayatullah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The study on the reformulation of the concept of nafaqah (financial support) in Islamic family law has become increasingly relevant amid the social and economic transformations brought about by the digital era and the expanding dual roles of women in both domestic and public spheres. This research aims to reanalyze the conceptual understanding of nafaqah based on the values of the Qur’an, taking into account the context of the digital economy and the transformation of modern family structures. The research employs a qualitative approach through library research, combining an analysis of classical texts in uṣūl al-fiqh and family fiqh with contemporary literature discussing maqāṣid al-sharīʿah and gender justice. The findings reveal that the concept of nafaqah in Islamic law encompasses interconnected moral, social, and economic dimensions. Normatively, nafaqah is the responsibility of the husband; however, within the context of the digital economy, this principle requires reinterpretation to align with the Qur’anic values of justice, reciprocity, and partnership. The integration of the principles of ḥifẓ al-māl (protection of wealth) and ḥifẓ al-nasl (protection of lineage) emphasizes that the reformulation of the concept of nafaqah is not merely a legal innovation but also part of a broader effort to preserve the welfare and sustainability of Muslim families in the modern era.